(untitled) (Herald of Journalism, 2016)
The article provides a comparative analysis of literature and journalism. Based on the study of the object and the subject, as well as methods of creative activity, showing the radio of literature and journalism, the audience, disclosed the specific of the first and second areas. Proven that if the main purpose of literature is the artistc and aesthetic representation of reality and spiritual world writers, for journalism is a demon.